Our Experience To Discover The Essence Of Pedagogical Facilitation - Baghdasaryan, Armine (Զանգակ հրատ.)
Today, the changes of the education system conditioned by the new strategy of education are aimed not only at the modernization of the content and methodological tools of education but also at the reconstruction of the whole characteristic /structure/ of the subject implementing those changes. In this article, we have tried to present pedagogical facilitation in the context of modern education, the requirements for a pedagogue who has mastered the technology of facilitation, the content of the pedagogue-facilitator activity, and the research carried out in two stages reveals how the image of the facilitator-teacher is perceived in the students' consciousness. The quantitative and qualitative features of the facilitator-pedagogues were given.
Keywords: Pedagogy